Kim Seon Ho, You Are Cancelled: The Collective Understanding of Cancel Culture - Cendera Rizky Bangun; Nareswari Kumaralalita (Fakultas Ilmu Komunikasi UKWMS, 2022)
On October 2021, Kim Seon Ho was on peak of his career when faced a wave of backlash after an anonymous post circulated in online communities saying that an unnamed actor “manipulated her into getting an abortion under false pretenses” and being cancelled. Researchers will use a case study of a Kim Seon Ho from South Korea who has been subjected to cancel culture in order to examine the complexity of this social phenomenon. This research tries to understand the cancel culture phenomenon that is not only happened in South Korea, but also USA, or other countries. Using FGD and also literature for data collection, this study explores how the responses from the participants’ expected to give meaning about regarding cancel culture. The result is some of participants agree with the cancel culture to be implemented, and some of them disagree. The conclusion is cancel culture can be a good thing when we want to make those who can be role model are those with positive attitudes. But on the other hand, cancel culture can be a bad thing when we place celebrity as a material commodity and get cancelled easily.